Custom and conflict in a Wealden village - Davie, N; Davie, Neil (1988)
This thesis aims to determine the relationship between demographic/ socio-economic and cultural change in an early modern English village. The village of Pluckley in the Weald of Kent was chosen for the richness of surviving documentation both at a regional and a parochial level. This has enabled Pluckley's experience over the 150-year period after 1550 to be located in the context of regional developments, thus permitting a fuller appreciation of the significance of such micro-history to the national life of the period. Pluckley's geographical location on the boundary between scarpland and wealden Kent resulted in a relative shortage of common, waste and forest suitable for encroachment or squatting. This spared the village the high levels of immigration found in many woodland-pasture communities, but considerable indigenous population growth during the 1590s-1620s needed to be accomodated. This required the sub-division of many existing holdings; a process made possible by the expansion of textile manufacture in the region. The result was two-fold: a consolidation in the position of small husbandmen and craftsmen in the village at the expense of more substantial landholders; and an increase in the numerical importance of Pluckley's poorest strata -labourers, cottagers, poor craftsmen and widows. Two responses to the interlocking demographic and economic crisis of the late sixteenth and early seventeenth centuries can be observed. One was the emigration of perhaps ten per cent of Pluckley's households in the three decades following the industrial crisis of 1630-1. The other was revealed in the apparent resentment of some village officeholders -many of them middling farmers not immune to the financial pressures of the period- to the increased burden posed by the expanding population of poor in the village. This resentment found expression in an attempt to tighten standards of sexual and marital conduct during the period 1590-1640. There is no evidence, however/ that sustained reforming activity in the village extended beyond sexual regulation to other 'disorders' associated by contemporaries with popular culture. Relatively low levels of poverty in the village (compared with elsewhere in mid-Kent) may have hindered the emergence of a powerful Puritan lobby bent on such reforms; though fissures within Pluckley's ruling elite as well as demographic and economic developments may have played their part in the continuing weakness of the 'godly' cause.